The Effectiveness of Group Counseling Cognitive Restructuring Techniques in Reducing Students' Late Learning Behavior - Felma, Felma; Silalahi, Micha Felayati (Universitas Negeri Medan, 2024)
The purpose of this study was to reduce students' late learning behavior through group counseling services with cognitive restructuring techniques. This research uses the type of action research carried out in two cycles. Each cycle consists of four stages, namely: Planning, action, observation, and reflection. The subjects of this study consisted of 5 students with the consideration that the subjects were often late for class. The type of action taken is the provision of group counseling services with cognitive restructuring techniques. Data collection techniques in this study used observation and interviews. The results of this study indicate that after implementing cycle I, the average percentage of late behavior following student learning has changed by 29.34%, while in cycle II the average percentage of late behavior following student learning has changed by 51.33%. The results of this study indicate the level of success of the implementation of actions in cycle II which has been improved based on the results of the reflection from cycle I. It can be concluded that through group counseling cognitive restructuring techniques can reduce the behavior of being late for student learning.